Peran Gereja dalam Mempersiapkan Utusan Injil ke Daerah-daerah di Indonesia: Sebuah Pemikiran Misiologis - Yanto Paulus Hermanto; Hizkia David Asaf Gultom; Kenny Gracia Howardy; Tomi Fransiskus Manullang (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
The survey results show that the church has played little role in sending missionaries to the regions. This is very concerning about the implementation of Christ's great commission. Therefore the authors researched how to maximize the role of the church in sending missionaries to the regions. Method for answering this research question, the authors use a qualitative approach. The discussion in this paper includes a shared perception of missionaries, the importance of the Church making missions, and how the church chooses and sends missionaries. From this discussion, it is obtained that the role of the church should be in sending missionaries to the regions.